Polishing solution for reducing CMP (Chemical Mechanical Polishing) defects of ruthenium barrier layer copper
By using the compound active agent of phosphate and sodium α-alkenylsulfonate in the polishing liquid, the problem of defect control after the copper CMP of the ruthenium barrier layer in the advanced technology node integrated circuit is solved, effectively reducing scratch, corrosion and contamination defects is achieved, and the surface quality of the integrated circuit is significantly improved.
Patent Information
- Application Number
- CN202411794663.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
In the manufacturing of advanced technology node integrated circuits, the difficulty of defect control after chemical mechanical polishing (CMP) of ruthenium barrier copper increases, and traditional technology cannot meet the defect requirements below 28nm.
A polishing liquid containing phosphate and sodium α-alkenylsulfonate is used to reduce defects such as scratches, corrosion and contamination through its synergistic effect, and effectively control the defects after CMP.
Compared with commercial polishing liquid, the new polishing liquid has reduced scratch defects by 80%, corrosion defects by 30%, and contamination defects by 60%, significantly improving the surface quality of the integrated circuit.
Smart Images

Figure CN119710708A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of advanced technology node integrated circuit manufacturing, in particular to the field of chemical mechanical polishing, and in particular to a method for reducing CMP surface defects of a multi-layer copper wiring ruthenium barrier layer. Background Art
[0002] With the development of integrated circuits, integrated circuits mostly use multi-layer wiring structures. At present, in advanced technology node integrated circuits below 14nm, the resistivity, stability and step coverage of traditional barrier layer materials are difficult to meet the needs; metal ruthenium (Ru) has better performance in the above mentioned aspects and is a new barrier layer material to replace Ta / TaN.
[0003] Chemical Mechanical Polishing (CMP) is critical to the performance of integrated circuit devices, and post-CMP defect control has become a global scientific and technological problem in integrated circuit manufacturing. Because it is a "subtractive" processing process, it can throw away excess materials. Therefore, once completed, it will present all the characteristics of the following circuits and defects. Moreover, in the semiconductor process flow, CMP is generally used as a downstream terminal process to complete the boundaries of a device or circuit. It not only produces its own defects but also needs to modify the defects produced by the previous process. When defects occur on the surface, the defects will cause the circuit to open or short, and the performance and stability will drift during the period. Therefore, the indicators of post-CMP defects are usually the most stringent in the entire process, because at this stage, defects can directly affect the yield and stability. Post-CMP defects mainly include scratches, corrosion, and contamination.
[0004] In response to this problem, "ZL201911184055.1 Alkaline polishing liquid for reducing CMP defects in multi-layer wiring copper interconnection barrier layers and its preparation method" uses the synergistic effect of the anionic surfactant dodecylbenzenesulfonic acid (DBSA) and the non-ionic surfactant isomeric alcohol polyoxyethylene ether (iAEO) to solve the 55-65nm Ta / TaN barrier layer copper CMP defect problem. However, in accordance with Moore's Law, the feature size decreases at a rate of 0.7 times / generation, while the number of integrated circuits on each silicon wafer increases at a rate of 2 times / generation, which requires the defect density to be reduced at a rate of 0.5 times / generation to ensure the stability of the yield; on the other hand, as the feature size decreases, the size of the defect becomes smaller, while the number increases. This makes it increasingly difficult to control surface defects in integrated circuits, and the original technology cannot meet the requirements for ruthenium barrier layer copper CMP defects below 28nm. Summary of the invention
[0005] The purpose of the present invention is to provide a polishing liquid for reducing copper CMP defects in ruthenium barrier layers in view of the limitations of current technologies. The polishing liquid does not contain BTA or other azole inhibitors, and uses phosphates to replace traditional toxic and carcinogenic azole inhibitors, which is green and environmentally friendly; compared with traditional AEO series polishing liquids, sodium α-olefin sulfonate has significantly improved cleaning and dispersing performance; through the synergistic effect of the two, defects such as scratches, corrosion, and contamination can be effectively controlled, thereby reducing post-CMP defects of integrated circuits at advanced technology nodes.
[0006] The present invention solves the technical problem by adopting the following technical solutions.
[0007] A polishing liquid for reducing copper CMP defects of a ruthenium barrier layer, the polishing liquid comprising: an activator, silicon dioxide, a chelating agent, an oxidant, a bactericide, a pH regulator and deionized water;
[0008] The content of each component is as follows, by mass percentage: active agent 0.001-4%, silicon dioxide 0.5-10%, chelating agent 0.02-2%, oxidant 0.02-5%, bactericide 0.03-2%, and the balance is deionized water;
[0009] The active agent is phosphate ester and sodium α-olefin sulfonate; the mass ratio is phosphate ester and sodium α-olefin sulfonate = 1-5:1;
[0010] The pH value of the polishing liquid is 6.0-11.5.
[0011] The chelating agent is specifically a mixture of one or more of glycine, glycine salt, citric acid, citrate, and ethylenediaminetetraacetate;
[0012] The fungicide is specifically a mixture of one or more of methylisothiazolinone, kasone, potassium sorbate, benzoic acid, 5-chloro-2-methyl-4-isothiazolin-3-one, and 1-2-benzisothiazolin-3-one;
[0013] The oxidant is hydrogen peroxide;
[0014] The phosphate ester is a mixture of one or more alcohol polyoxyethylene ether phosphate esters (PEO-P) or isomeric alcohol polyoxyethylene ether phosphate esters, wherein the polyoxyethylene (EO) chain length is 5-12 and the carbon chain is 7-18; the α-olefin sodium sulfonate is a surfactant with a carbon chain of 12-18.
[0015] The pH value adjusting agent is specifically 6.0-11.5;
[0016] The application method of the polishing liquid for reducing copper CMP defects of the ruthenium barrier layer comprises the following steps:
[0017] Adding polishing liquid into a polishing machine to polish the ruthenium barrier layer pattern sheet to obtain a finished product;
[0018] Among them, the polishing conditions are: working pressure is 1-5Psi, polishing head speed is 88-108r / min, polishing disc speed is 100-110r / min, and polishing liquid flow rate is 200-300ml / min.
[0019] The beneficial effects of the present invention are:
[0020] The present invention uses a polishing liquid containing a compound active agent of phosphate and sodium α-olefin sulfonate to polish the copper wiring of the ruthenium barrier layer of the integrated circuit of the advanced technology node, and solves the scratch defects of hard particles or large particles by soft packaging technology, reducing the number of large particles, moving to mixed lubrication, increasing the water absorption of the polishing pad to soften the soft pad, and assisting in removing the particles and polishing byproducts of the polishing pad, etc., which reduces the scratch defects by 80% compared with commercial polishing liquid; controls the corrosion defects by the synergistic effect of the active agent, and reduces the corrosion defects by 30% compared with commercial polishing liquid without adding toxic carcinogenic inhibitors such as BTA; and controls the contamination defects by the principle of preferential adsorption based on the lower surface tension of the compound active agent, which reduces the contamination defects by 60% compared with commercial polishing liquid. Finally, the scratch, corrosion and contamination defects after CMP are effectively controlled, and the key problem of integrated circuit manufacturing is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 is the surface tension of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3;
[0023] Figure 2 The zeta potential and LPC after polishing of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are compared;
[0024] Figure 3 The polishing friction coefficients of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are compared;
[0025] Figure 4 The surface roughness comparison after polishing of Example 1 and Comparative Example 4;
[0026] Figure 5 The surface states of Example 1, Comparative Example 1 and Comparative Example 4 after polishing are compared;
[0027] Figure 6 Schematic diagram of the principle of controlling surface defects using E1310P and α-AOS.
[0028] Figure 7 The figure is a comparison of the number of defects after polishing in Example 1, Comparative Example 1 and Comparative Example 4. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to specific embodiments.
[0031] The embodiment of the present invention provides a method for reducing copper CMP defects of a ruthenium barrier layer of a multi-layer copper wiring, comprising the following steps:
[0032] A polishing liquid containing phosphate and sodium α-olefin sulfonate is prepared; the polishing liquid is added into a polishing machine to polish the graphic sheet to obtain a finished product;
[0033] The polishing conditions are as follows: working pressure is 1-5Psi, polishing head speed is 88-108r / min, polishing disc speed is 100-110r / min, and polishing liquid flow rate is 200-300ml / min.
[0034] The polishing liquid containing phosphate and sodium α-olefin sulfonate compound activator is used to polish the copper wiring of the ruthenium barrier layer of integrated circuits at advanced technology nodes. The hard particles or large particles are soft-wrapped, the number of large particles is reduced, the mixture is moved to mixed lubrication, the water absorption of the polishing pad is increased to soften the soft pad, and the particles and polishing byproducts of the polishing pad are assisted to remove the particles. The corrosion defects are controlled by the synergistic effect of the activator; the contamination defects are controlled by the principle of preferential adsorption based on the lower surface tension of the compound activator. Finally, the scratch, corrosion and contamination defects after CMP are effectively controlled, and the key problems of integrated circuit manufacturing are overcome.
[0035] In some embodiments of the present invention, the phosphate ester includes one or more mixtures of alcohol polyoxyethylene ether phosphate (PEO-P) or isomeric alcohol polyoxyethylene ether phosphate, wherein the polyoxyethylene (EO) chain length is 5-12 and the carbon chain is 7-18; the sodium α-olefin sulfonate is a surfactant with a carbon chain of 12-18.
[0036] In some embodiments of the present invention, the components of the polishing liquid are, by mass percentage, 0.5-10% silica sol, 0.02-2% chelating agent, 0.02-5% oxidant, 0.001-4% phosphate fatty acid methyl ester ethoxylate, 0.03-2% bactericide, and the balance deionized water.
[0037] In some embodiments of the present invention, the pH value of the polishing liquid is 6.0-11.5.
[0038] In some embodiments of the present invention, the particle size of the silica sol is 30nm-200nm. The nano-scale silica sol abrasive mainly provides mechanical action during the CMP process. Abrasives with appropriate particle size play an important role in polishing rate, surface roughness, and surface defects.
[0039] In some embodiments of the present invention, the chelating agent is a mixture of one or more of glycine, glycine salt, citric acid, citrate, ethylenediaminetetraacetate, etc. The oxidizing agent is a mixture of one or more of peroxide, transition metal salts, nitric acid and nitrate, halogen oxyacid salt, etc. The chelating agent and oxidizing agent react chemically with copper, play a chemical role in the CMP process, and are the main factors in the copper removal rate.
[0040] In some embodiments of the present invention, the bactericide is a mixture of one or more of methylisothiazolinone, kason, potassium sorbate, benzoic acid, 5-chloro-2-methyl-4-isothiazolin-3-one, and 1-2-benzisothiazolin-3-one. The bactericide can sterilize the polishing liquid and effectively extend the service life of the polishing liquid.
[0041] In some embodiments of the present invention, the preparation method of the polishing liquid comprises the following steps: taking silica sol, adding deionized water to dilute, and obtaining a silica sol solution; mixing a chelating agent, an oxidant, a phosphate ester and a fatty acid methyl ester ethoxylate compound active agent, and a bactericide, and diluting with deionized water, and then adding the silica sol solution, stirring evenly to obtain a polishing liquid. The preparation method has a simple process, can produce a polishing liquid with good stability, and is suitable for the needs of large-scale industrial production.
[0042] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0043] Example 1
[0044] A method for reducing surface defects in ruthenium barrier copper CMP of multi-layer wiring of advanced technology node integrated circuits comprises the following steps:
[0045] Prepare 10 kg of polishing liquid: take 250 g of silica sol with a mass percentage concentration of 40%, wherein the particle size of silicon dioxide is 80 nm, add deionized water to dilute to 5 kg, and obtain a silica sol solution; mix glycine, hydrogen peroxide, isomeric tridecanol polyoxyethylene ether phosphate E1310P, sodium α-olefin sulfonate (c=16), and a fungicide and add deionized water to dilute to 5 kg to obtain a second solution (the mass percentage of each substance in the second solution is: 2% glycine, 0.9% hydrogen peroxide, 0.03% isomeric tridecanol polyoxyethylene ether phosphate E1310P, 0.01% sodium α-olefin sulfonate (c=16), 0.5% fungicide), then add the above silica sol solution to the second solution, stir evenly to obtain a polishing liquid, adjust the pH value of the polishing liquid to 7.5 with KOH or phosphoric acid, and set aside;
[0046] The above-mentioned phosphate E1310P and α-olefin sulfonate sodium α-AOS have the following molecular formulas:
[0047]
[0048] The above-mentioned fungicide is a 1:1 mixture of methylisothiazolinone and benzoic acid;
[0049] Among them, the hydrophilic group of E1310P can be adsorbed on the copper surface during the CMP process to form a denser inhibitory film to replace the role of traditional inhibitors; α-AOS is an excellent anionic surfactant with good biodegradability, low irritation, low toxicity, good foaming properties, and is widely used in daily products with low toxicity. E1310P and α-AOS have similar carbon chains, so they can be adsorbed to each other through hydrocarbon chain interactions.
[0050] Polishing: Add the polishing liquid into the Universal-300Plus polishing machine produced by Huahaiqing Technology, and polish the copper film under the conditions of working pressure Z1: 4.76Psi, Z2: 2.01Psi, Z3: 1.82Psi, Z4: 1.92Psi, Z5: 1.63Psi; polishing head speed of 98r / min; polishing disc speed of 105r / min; polishing liquid flow rate of 250ml / min. Copper film crystal phase <100> , the process is standard magnetron sputtering, film thickness: 100nm, purity: 99.99%.
[0051] Comparative Example 1
[0052] Compared with Example 1, the polishing liquid does not contain phosphate E1310P and sodium α-olefin sulfonate α-AOS.
[0053] Comparative Example 2
[0054] In Comparative Example 2, compared with Example 1, the polishing liquid only contains phosphate E1310P and does not contain α-AOS, and the mass fraction of the active agent is the same as that of Example 1.
[0055] Comparative Example 3
[0056] Compared with Example 1, Comparative Example 3 is a polishing liquid containing only α-AOS and no phosphate E1310P, and the mass fraction of the active agent is the same as that of Example 1.
[0057] Comparative Example 4
[0058] Compared with Example 1, Comparative Example 4 uses commercial polishing liquid for polishing.
[0059] Test Example 1
[0060] The surface tension, large particle test / Zeta potential, friction during polishing, roughness after polishing, and surface state test of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were compared. The results are as follows: Figure 1-5 shown.
[0061] From the attached Figure 1 It can be seen that the surface tension of the polishing liquid with added surfactant is lower than that of the polishing liquid without added surfactant, and the surface tension of the polishing liquid compounded with E1310P and α-AOS is significantly lower than that of the single surfactant.
[0062] From the attached Figure 2 It can be seen that the absolute value of Zeta potential of the blank control group in Comparative Example 1 is the smallest and the number of large particles is the largest. The addition of E1310P to Comparative Example 2 is conducive to the increase of the absolute value of Zeta potential. The addition of α-AOS to Comparative Example 2 is more conducive to reducing the number of large particles. After adding the compound active agent in Example 1, better Zeta potential and LPC can be obtained.
[0063] The pH value of the polishing liquid is 7.5, SiO 2 The particle surface is composed of silanol groups and hydroxyl groups, and the colloid surface is negatively charged. E1310P will ionize in the solution to generate E1310P - Ion, E1310P - The anionic group is a hydrophobic group and will adsorb on SiO 2 Particle surface, such as Figure 6 Zeta potential is the potential difference between the slip plane and the bulk phase of the solution. - The adsorption of SiO 2The negative charge carried by the stern layer and diffusion layer of the particles increases, and the total amount of negative charge increases, resulting in a larger absolute value of the potential. The value of the Zeta potential is related to the stability of the silica sol dispersion. The larger the absolute value of the Zeta potential, the more stable the system. α-AOS can adsorb on the surface of the particles, increase the spatial repulsion between the particles, and reduce the number of large particles in the solution. E1310P can better enhance the electrostatic repulsion between the particles, and sodium α-olefin sulfonate is more conducive to enhancing the spatial repulsion between the particles. Taking all factors into consideration, better stability can be obtained under the compounding conditions, and the electrostatic force and spatial repulsion between the particles are improved to a certain extent.
[0064] Attached Figure 3 The friction coefficient and friction force changes during the CMP process. In Comparative Example 1, no activator was added to the polishing liquid. As the polishing progressed, the friction force and friction coefficient showed an upward trend. At the end of polishing, the friction coefficient reached 0.5822. When E1310P was added to Comparative Example 2, the initial friction coefficient remained almost unchanged, and the friction coefficient was 0.4820 at 180s; after sodium α-olefin sulfonate was added to Comparative Example 3, the friction factor was 0.4590 at 180s; compared with Comparative Example 1, the friction factors of both showed a downward trend. In Example 1, E1310P was compounded with α-AOS, and the friction factor at each polishing period showed a further downward trend.
[0065] Attached Figure 4 The AFM images of the Cu surface after polishing with different polishing solutions are shown. The root mean square height (Sq) is used to represent the roughness of the Cu surface. Figure (a) shows the surface of the Cu after polishing in the blank group, with an Sq of 18.5nm; Figure (b) shows the surface of the Cu after polishing with the E1310P polishing solution, with an Sq of 2.63nm; Figure (c) shows the surface of the Cu after polishing with the α-AOS polishing solution, with an Sq of 20.0nm. The addition of sodium α-olefin sulfonate slightly increases the rate of solution wettability enhancement, so the local reaction is stronger; Figure (d) shows the surface of the Cu after polishing under the compound condition, with an Sq of 1.90nm. Obviously, the surface quality of the compound of E1310P and α-AOS is better.
[0066] Attached Figure 5The SEM images of the Cu surface are shown in Figure (a) after the blank group is immersed in the solution for 1 min. The Cu surface has dense corrosion marks and obvious corrosion pits, the local flattening is very poor, and the chemical reaction is relatively violent. As shown in Figure (b), after the Cu surface is immersed in the solution containing E1310P, there is a dense Cu-E1310P inhibition film, no obvious corrosion marks, the oxidation and complexation reactions of Cu are inhibited, and the surface quality is good. As shown in Figure (c), after the Cu surface is immersed in the solution containing α-AOS, there are certain corrosion marks on the Cu surface, but the degree of corrosion is controlled to a certain extent. Combined with the electrochemical experiment, it is concluded that α-AOS is adsorbed on the surface by physical action, and its protection ability for Cu is weak. As shown in Figure (d), after the Cu surface is immersed in the solution containing E1310P and α-AOS composite active agent, there are almost no obvious corrosion marks, indicating that E1310P and α-AOS have a good protective effect on the surface under the synergistic effect.
[0067] In the attached Figure 2-4 It can be seen that E1310P and α-AOS work synergistically to reduce the surface tension of the polishing liquid, improve the dispersion of the polishing liquid, and improve the surface state after polishing.
[0068] Test Example 2
[0069] Attached Figure 7 Compare the total defects after CMP of different polishing solutions of Example 1, Example 2 and Example 4. Slurry 1 is Example 1 without active agent; slurry 2 is commercial polishing solution, i.e., Example 4; and slurry 3 is Example 1 containing E1310P and α-AOS compound active agent. The results show that the defects of Example 1 can effectively control scratches, corrosion, and contamination, and the defects after CMP of commercial polishing solution are significantly reduced. Its main mechanism is:
[0070] (1) Control scratch defects
[0071] (a) According to the Langmuir adsorption theory, E1310P and α-AOS are mixed with active agents to form particles with high hardness or large particles through soft coating technology (such as attachment). Figure 7 ), modify the abrasive in the grinding liquid and reduce the hardness.
[0072] (b) E1310P and α-AOS have similar relative hydrocarbon chain lengths, and their hydrocarbon chains interact strongly. The synergistic effect between them enhances the adsorption between them. Under the action of spatial forces, the adsorbed surfactant layer helps to keep the particles at a larger separation distance, thereby reducing the van der Waals attraction between the particles. This increases the absolute value of the zeta potential of the grinding liquid, improves the particle size dispersion of the Chinese silica sol in the grinding liquid, and reduces the LPC. Figure 2 shown.
[0073] (c) CMP is a "chemical boundary lubrication process (CBL process)", which changes from boundary lubrication on the Stribeck curve to mixed lubrication during the polishing process. Figure 3 In the experiment, the addition of surfactants reduced the friction coefficient COF (COF), especially the combination of 1310P and α-AOS, which shifted the tribological mechanism of the Stribeck curve to the mixed lubrication zone, which was beneficial to reduce the scratch defects.
[0074] (d) Increase the water absorption of the polishing pad through its good penetration and wetting ability. The compound active agent has good penetration and wetting ability, and its branched hydrophobic chain enhances the wetting ability. According to the Washburn equation,
[0075]
[0076] Water molecules penetrate the pores through capillary action, and a more hydrophilic pad surface leads to a higher water absorption rate. Since the grinding pad is a high-molecular polyurethane viscoelastic material, water absorption causes the hardness of the polyurethane polymer in the polishing pad to decrease monotonically with the increase in water absorption rate, and the viscoelastic ratio is smaller. It tends to store energy rather than lose energy during the CMP process, ultimately making the friction of the polishing pad in contact with the wafer during the CMP process softer, which is beneficial to reducing scratch defects.
[0077] (e) During the CMP process, abrasive particles and polishing byproducts penetrate into the polishing pad, increasing the hardness of the polishing pad and thus increasing scratch defects. However, using the developed barrier layer slurry, α-AOS molecules can be quickly adsorbed on the polishing pad surface and polishing byproducts; the rapid adsorption efficiency of α-AOS causes surfactant molecules to attach to the polishing pad and polishing byproduct surfaces. This enables them to participate in direct mechanical contact between the wafer, the polishing pad surface and the sodium α-olefin sulfonate, and generate greater shear forces, which can remove particles and byproducts from the polishing pad surface during the dresser dressing process.
[0078] In summary, the combination of 1310P and α-AOS can effectively solve the scratch defects of hard particles or large particles through soft packaging technology, reducing the number of large particles, moving to mixed lubrication, increasing the water absorption of the polishing pad to soften the soft pad, and assisting in removing particles and polishing by-products from the polishing pad.
[0079] (2) Controlling corrosion defects through the synergistic effect of E1310P and α-AOS
[0080] In addition to scratches, corrosion is also a common defect in CMP of integrated circuit multilayer wiring. Currently, commercial polishing fluids usually control corrosion defects by adding inhibitor BTA, but BTA and copper will form insoluble Cu (n) BTA, more importantly, is toxic and not environmentally friendly.
[0081] like Figure 6 As shown, this patent uses E1310P and α-AOS compound active agent to control corrosion defects. E1310P is adsorbed on the Cu surface by chemical and physical mixed adsorption. E1310P and Cu will generate new substances as an inhibitory film. On the one hand, the polar hydrophilic group of E1310P will dissociate in the solution to form E1310P. - In the form of E1310P - Will and Cu2 + The ions form Cu-E1310P passivation, which adheres to the Cu surface. The exposed Cu decreases, which inhibits the oxidation of Cu to a certain extent. On the other hand, the isoelectric point (IEP) of CuO is greater than the pH value of the solution, and it is positively charged in the solution. Due to the effects of static electricity and hydrophobic groups, E1310P - It is physically adsorbed on the CuO surface, inhibiting the subsequent reaction of CuO to a certain extent. Under the synergy of chemical and physical effects, E1310P will form a dense adsorption layer on the Cu surface, so with the addition of E1310P, the removal rate and static corrosion rate of Cu become smaller. α-AOS itself also has hydrophilic and hydrophobic groups, so α-AOS will also form an adsorption film on the Cu surface. When α-AOS exists in E1310P - When between, you can isolate E1310P - The electrostatic repulsion between particles makes E1310P - The tighter arrangement forms a denser joint inhibition film. Because E1310P and α-AOS are physically adsorbed, they are relatively easy to remove, so they can better control corrosion defects than BTA; in addition, they are also green and environmentally friendly.
[0082] (3) Control contamination defects
[0083] Contamination defects are also common defects in CMP of integrated circuit multilayer wiring. There are high-density, highly active dangling bonds on the surface after CMP; the surface of the material just after CMP is very easy to absorb surrounding contaminants. Even if all external impurities are eliminated, by-products will be produced during the CMP process, so the polishing liquid itself needs to have the ability to prevent contaminants from adhering to the wafer.
[0084] The Gibbs surface free energy of a liquid measures the increase in the Gibbs energy per unit area of the surface system under constant temperature and pressure conditions, that is,
[0085] dG=γdA+Adγ (14)
[0086] In the formula, G is the surface Gibbs free energy of the liquid; A is the surface area of the object; γ is the surface tension. It can be seen that under constant temperature and pressure conditions, the factor affecting surface energy is mainly the surface tension of the liquid.
[0087] Surfactants added to the polishing liquid can be preferentially adsorbed on the copper surface to reduce surface free energy by reducing surface tension. Since surfactant molecules have both hydrophilic and lipophilic groups, their molecular structures have asymmetric and polar characteristics, so that the hydrophilic groups in the CMP process can be attracted by water molecules in the polishing liquid, while the lipophilic groups are repelled by water molecules. In order to overcome this unstable state, the lipophilic groups only occupy the surface of copper and contaminants, and extend the hydrophilic groups into the polishing liquid, with the hydrophilic groups and hydrophobic groups at both ends to form an asymmetric structure. The chemical adsorption of contaminants on the wafer surface can be controlled by reducing surface tension and surface free energy.
[0088] The surface tension of the polishing liquid with the addition of surfactants is significantly reduced, so the surface force field strength is higher, and it is preferentially adsorbed on the surface of the wafer and other substances. This adsorption is physical adsorption, which prevents impurity particles from contacting the "clean" wafer surface and undergoing chemical adsorption; its decomposition process is simple, and the "coated" particles formed can be easily detached from the wafer surface and removed under the action of post-CMP cleaning agents and cleaning equipment, which brings convenience to the subsequent post-CMP cleaning surface.
[0089] As attached Figure 2 As shown, the E1310P and α-AOS compound surfactant in Example 1 has significantly lower surface tension and better adsorption effect, thus better control of contamination defects.
[0090] In summary, the E1310P and α-AOS compound active agent can solve the scratch defects of hard particles or large particles through soft wrapping technology, reduce the number of large particles, move to mixed lubrication, increase the water absorption of the polishing pad to soften the soft pad, and assist in removing the particles and polishing byproducts of the polishing pad; the synergistic effect of E1310P and α-AOS can control corrosion defects; E1310P and α-AOS have lower surface tension and use the principle of preferential adsorption to control contamination defects. In the end, the scratch, corrosion and contamination defects after CMP are effectively controlled, and the surface defects of ruthenium barrier copper CMP are finally overcome.
[0091] Table 1
[0092]
[0093] Therefore, the present invention provides a method for effectively reducing copper CMP surface defects of barrier layers of integrated circuits at advanced technology nodes.
[0094] Example 2
[0095] The other steps are the same as those in Example 1, except that the chelating agent is replaced by 0.9% citric acid instead of 2% glycine; the bactericide is replaced by a 7:3 mixture of 5-chloro-2-methyl-4-isothiazoline-3-one and 1-2-benzisothiazolin-3-one instead of a 1:1 mixture of methylisothiazolinone and benzoic acid; the phosphate is replaced by E1310P with alcohol polyoxyethylene ether phosphate (PEO-P), wherein the polyoxyethylene (EO) chain length is 7 and the carbon chain is 14; the carbon chain of α-olefin sodium sulfonate is replaced by 16 to 14. (The total mass ratio of bactericide and active agent remains unchanged)
[0096] The polishing pressure is reduced to Z1: 3.27Psi, Z2: 1.97Psi, Z3: 1.44Psi, Z4: 1.4Psi, Z5: 1.32Psi; the polishing head speed is changed from 98r / min to 96r / mn; the polishing disc speed is changed from 105r / min to 103r / min; the polishing liquid flow rate is changed from 250ml / min to 200ml / min.
[0097] The zeta potential and LPC of the polishing solution, the polishing friction coefficient, and the surface roughness after polishing are close to those in Example 1. The number of surface defects of the ruthenium barrier copper CMP is 79.
[0098] Example 3
[0099] The other steps are the same as those in Example 1, except that the chelating agent is replaced by 2% glycine with a mixture of glycine and copper glycinate in a ratio of 3:1 (the mass ratio of the chelating agent in the second solution is 1.2%); the bactericide is replaced by a mixture of methylisothiazolinone and benzoic acid in a ratio of 1:1 with a mixture of methylisothiazolinone, kasone, and potassium sorbate in a ratio of 1:2:7; the phosphate is replaced by E1310P with a mixture of E1410P and E1310P in a ratio of 1:1, wherein the polyoxyethylene (EO) chain length is 10, and the carbon chains are 14 and 13 respectively; the carbon chain of α-olefin sodium sulfonate is replaced by 16 with 12. (The total mass ratio of bactericide and active agent remains unchanged)
[0100] The polishing pressure changes to Z1: 4.41Psi, Z2: 2.07Psi, Z3: 1.99Psi, Z4: 1.77Psi, Z5: 1.44Psi; the polishing head speed is changed from 98r / min to 88r / mn; the polishing disc speed is changed from 105r / min to 106r / min; the polishing liquid flow rate is changed from 250ml / min to 225ml / min.
[0101] The zeta potential and LPC of the polishing solution, the polishing friction coefficient, and the surface roughness after polishing are close to those in Example 1. The number of defects on the copper CMP surface of the ruthenium barrier layer is 91.
[0102] Example 4
[0103] The other steps are the same as those in Example 1, except that the chelating agent is replaced by 2% glycine with a mixture of glycine and ethylenediaminetetraacetic acid in a ratio of 1:6 (the mass ratio of the chelating agent in the second solution is 0.7%); the bactericide is replaced by a mixture of methylisothiazolinone and benzoic acid in a ratio of 1:1 with kasone, potassium sorbate, and benzoic acid in a ratio of 1.5:1:1; the phosphate is replaced by E1310P with alcohol polyoxyethylene ether phosphate (PEO-P), wherein the polyoxyethylene (EO) chain length is 6 and the carbon chain is 12; the carbon chain of α-olefin sodium sulfonate is replaced by 16 with 12. (The total mass ratio of bactericide and active agent remains unchanged)
[0104] The polishing pressure changes to Z1: 4.11Psi, Z2: 2.09Psi, Z3: 2.72Psi, Z4: 2.03Psi, Z5: 1.17Psi; the polishing head speed is changed from 98r / min to 106r / mn; the polishing disc speed is changed from 105r / min to 110r / min; the polishing liquid flow rate is changed from 250ml / min to 220ml / min.
[0105] The zeta potential and LPC of the polishing solution, the polishing friction coefficient, and the surface roughness after polishing are close to those in Example 1. The number of surface defects of the ruthenium barrier copper CMP is 79.
[0106] Example 5
[0107] The other steps are the same as those in Example 1, except that the chelating agent is replaced by 2% glycine with a 4:1:2 mixture of citric acid, sodium citrate and ethylenediaminetetraacetic acid (the mass ratio of the chelating agent in the second solution is 1.9%); the bactericide is replaced by a 1:1 mixture of methylisothiazolinone and benzoic acid with 5-chloro-2-methyl-4-isothiazolin-3-one; the phosphate is replaced by E1310P with alcohol polyoxyethylene ether phosphate (PEO-P), in which the polyoxyethylene (EO) chain length is 9 and the carbon chain is 15; the carbon chain of α-olefin sodium sulfonate is replaced by 16 to 15. (The total mass ratio of bactericide and active agent remains unchanged)
[0108] The polishing pressure changes to Z1: 4.29Psi, Z2: 3.9Psi, Z3: 2.66Psi, Z4: 2.59Psi, Z5: 1.94Psi; the polishing head speed is changed from 98r / min to 100r / mn; the polishing disc speed is changed from 105r / min to 104r / min; the polishing liquid flow rate is changed from 250ml / min to 210ml / min.
[0109] The zeta potential and LPC of the polishing solution, the polishing friction coefficient, and the surface roughness after polishing are close to those in Example 1. The number of surface defects of the ruthenium barrier copper CMP is 53.
[0110] Example 6
[0111] The other steps are the same as those in Example 1, except that the chelating agent is replaced by 2% glycine with a 1:1 mixture of citric acid and glycine (the mass ratio of the chelating agent in the second solution is 1.8%); the bactericide is replaced by a 1:1 mixture of methylisothiazolinone and benzoic acid with a 1:9 mixture of potassium sorbate and 1-2-benzisothiazolin-3-one 5-chloro-2-methyl-4-isothiazolin-3-one; the phosphate is replaced by E1310P with a 1:3 mixture of alcohol polyoxyethylene ether phosphate (PEO-P) and isomeric alcohol polyoxyethylene ether phosphate, wherein the chain length of polyoxyethylene (EO) is 11 and the carbon chain is 17; the carbon chain of α-olefin sodium sulfonate is replaced by 16 with 18. (The total mass ratio of bactericide and active agent remains unchanged)
[0112] The polishing pressure changes to Z1: 3.89Psi, Z2: 3.62Psi, Z3: 2.73Psi, Z4: 2.69Psi, Z5: 1.67Psi; the polishing head speed is changed from 98r / min to 100r / min; the polishing disc speed is changed from 105r / min to 104r / mn; the polishing liquid flow rate is changed from 250ml / min to 245ml / min.
[0113] The zeta potential and LPC of the polishing solution, the polishing friction coefficient, and the surface roughness after polishing are close to those in Example 1. The surface defect of the ruthenium barrier copper CMP is 99.
[0114] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0115] Matters not covered by the present invention are known technologies.
Claims
1. A polishing liquid for reducing copper CMP defects in a ruthenium barrier layer, characterized by The polishing liquid comprises: an active agent, silicon dioxide, a chelating agent, an oxidant, a bactericide, a pH regulator and deionized water; The content of each component is as follows, by mass percentage: active agent 0.001-4%, silicon dioxide 0.5-10%, chelating agent 0.02-2%, oxidant 0.02-5%, bactericide 0.03-2%, and the balance is deionized water; The active agent is phosphate ester and sodium α-olefin sulfonate; the mass ratio is phosphate ester and sodium α-olefin sulfonate = 1-5:1; The pH value of the polishing liquid is 6.0-11.
5.
2. The polishing liquid for reducing copper CMP defects in a ruthenium barrier layer as claimed in claim 1, wherein the chelating agent is a mixture of one or more of glycine, glycine salts, citric acid, citrates, and ethylenediaminetetraacetate.
3. The polishing liquid for reducing copper CMP defects in a ruthenium barrier layer according to claim 1, characterized in that The fungicide is specifically a mixture of one or more of methylisothiazolinone, kasone, potassium sorbate, benzoic acid, 5-chloro-2-methyl-4-isothiazolin-3-one, and 1-2-benzisothiazolin-3-one.
4. The polishing liquid for reducing copper CMP defects in a ruthenium barrier layer according to claim 1, characterized in that The oxidant is hydrogen peroxide.
5. The polishing liquid for reducing copper CMP defects of a ruthenium barrier layer according to claim 1, wherein the phosphate ester is a mixture of one or more of alcohol polyoxyethylene ether phosphate esters (PEO-P) or isomeric alcohol polyoxyethylene ether phosphate esters, wherein the polyoxyethylene (EO) chain length is 5-12 and the carbon chain is 7-18; The sodium α-olefin sulfonate is a surfactant with a carbon chain of 12-18.
6. The method for using the polishing liquid for reducing copper CMP defects in a ruthenium barrier layer according to claim 1, characterized in that The following steps are involved: Adding polishing liquid into a polishing machine to polish the ruthenium barrier layer pattern sheet to obtain a finished product; Among them, the polishing conditions are: working pressure is 1-5Psi, polishing head speed is 88-108r / min, polishing disc speed is 100-110r / min, and polishing liquid flow rate is 200-300ml / min.
Citation Information
Patent Citations
Alkaline polishing slurry for reducing CMP defects in multilayer copper interconnect barrier layers and its preparation method
CN111004579B